login
A173332
a(n) = a(n-2) + a(n-3) - floor(a(n-4)/2) - floor(a(n-6)/2).
1
1, 1, 1, 2, 2, 3, 4, 4, 6, 6, 7, 9, 8, 11, 11, 12, 15, 14, 18, 18, 20, 23, 22, 27, 26, 29, 32, 31, 37, 36, 39, 44, 41, 50, 48, 51, 59, 52, 66, 61, 65, 76, 64, 85, 75, 81, 96, 76, 108, 90, 99
OFFSET
0,4
COMMENTS
The first negative term is a(82) = -69.
LINKS
MATHEMATICA
f[-4] = 0; f[-3] = 0; f[-2] = 0; f[-1] = 0; f[0] = 1; f[1] = 1;
f[n_] := f[n] = f[n - 2] + f[n - 3] - Floor[f[n - 4]/2] - Floor[f[n - 6]/2]
Table[f[n], {n, 0, 50}]
nxt[{a_, b_, c_, d_, e_, f_}]:= {b, c, d, e, f, e+d-Floor[c/2]-Floor[a/2]}; NestList[ nxt, {1, 1, 1, 2, 2, 3}, 50][[All, 1]] (* Harvey P. Dale, Sep 18 2020 *)
CROSSREFS
Sequence in context: A338517 A173633 A138369 * A348526 A138374 A029936
KEYWORD
sign,easy
AUTHOR
Roger L. Bagula, Nov 22 2010
STATUS
approved